SIMBOL KOMUNIKASI DAN EMOSI - Parapat, Nelson Halong (Jurnal Insani, 2020)
This paper aims to provide insightful knowledge to readers about how human behavior which is a symbol of communication, both verbal and nonverbal, expresses emotions in relationships or relationships between humans. In our daily communication activities, both intentionally and unintentionally, we express our emotions when communicating with others from childhood to the end of our lives. We learn to channel and express emotions through the people around us. Expression of emotions in communication is done through various messages that are packaged using verbal symbols and nonverbal symbols. Verbal symbols are symbols in the form of words and a series of words (sentences) both spoken and written. Nonverbal symbols are all symbols that are not in the form of words, such as kinesics (body movements), facial expressions and eye gaze. There are various expressions of emotion. There are natural expressions without being bound by culture that are universal, there are contextual ones bound by cultural rules. In addition, although there are universal expressions of human emotions, it is not universal when and in what situations humans express these emotions because it is controlled by local cultural norms.